결구배추 잎의 이화학적 성분 조성 - 성기운(Gi-Un Seong); 황인욱(In-Wook Hwang); 정신교(Shin-Kyo Chung) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2016)
To increase the consumption of head-type kimchi cabbage leaves as fresh food ingredients, the physicochemical composition was investigated depending on leaf parts. Kimchi cabbage leaves were divided into three portions, such as outer (L1), mid (L2), and inner (L3), and their proximate compositions were determined along with dietary fiber, free sugar, organic acid, free amino acid, and mineral contents. Contents of moisture, crude protein, and crude fat were highest in L1, whereas contents of crude ash and carbohydrate were highest in L3 (P<0.05). Calories ranged 24.5~26.5 kcal/100 g with no significant difference among leaf parts, and dietary fiber content of L1 was highest (P<0.05). Fructose, glucose, and sucrose contents were highest in L3 (P<0.05). Citric acid, malic acid, and succinic acid were detected, and contents of citric acid and malic acid were highest in L3, in contrast, succinic acid was highest in L1 (P<0.05). Glutamic acid, constituting over 30% of the total free amino acid contents, was highest in L3, whereas ${γ}-aminobutyric$ acid contents were highest in L1 (P<0.05). K, Na, Ca, and Mg were the major minerals in head-type kimchi cabbage, and their contents showed no significant differences (P<0.05). It can be proposed that marketing of head-type kimchi cabbage as a fresh-cut vegetable could be enhanced due to the different quality characteristics of its leaf parts. 김치용 결구배추를 겉잎(L1), 중잎(L2), 속잎(L3)으로 세 등분하여 부위별로 일반성분을 포함한 이화학적인 성분을 측정하여 비교하였다. 조단백질 및 조지방 함량은 겉잎(L1)이 높았고, 조회분 및 탄수화물 함량은 속잎(L3)이 높았다(P<0.05). 열량은 24.5~26.5 kcal/100 g이었고 부위별로 유의적인 차이가 없었으며, 총식이섬유는 겉잎(L1)이 가장 높았다(P<0.05). 유리당은 fructose, glucose, sucrose가 확인되었으며, 속잎(L3)에서 fructose 및 glucose 함량이 높았다(P<0.05). 유기산은 citric acid, malic acid, succinic acid가 검출되었으며, citric acid와 malic acid 함량은 속잎(L3)이 높았고 succinic acid는 겉잎(L1)이 높았다(P<0.05). 총유리 아미노산의 30% 이상을 차지하는 glutamic acid 함량은 속잎(L3)에서 높았으며, ${γ}-aminobutyric$ acid의 함량은 겉잎(L1)이 가장 높았다(P<0.05). 결구배추 잎의 주요 미네랄 성분은 K, Na, Ca, Mg이며, 이 중 K의 함량이 가장 높았다. 총미네랄 함량은 겉잎(L1)이 가장 높았다(P<0.05). 결구배추 잎은 부위에 따라 이화학적 성분 조성이 다른 특성을 가지므로 신선편의 식재료로서 활용성이 더욱 증대될 수 있을 것으로 생각한다.